Management of Major Emergency Non Traumatic Urologic: An Experience of University Hospital of Cotonou - AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; SOUMANOU, Fouad Kolawale Yde; Lossitode, Fidèle; Hodonou, Fred Dètondji; Gandaho, Isidor Kokou Elvick; Dandjlessa, Olivier Armand (My University, 2018)
Objectives: The aim of this study was to determine the prevalence and management of the main non traumatic urological emergencies in the teaching university hospital of Cotonou in Benin Republic. Methods: In one year, we collected 76 cases. Patients under age 15 years old did not included in the study. Selected patients those who have supported by the Pediatric surgery department and all patients who have admitted for urological emergency in a traumatically context. The following items have studied: prevalence, age, sex, complaints, emergency type, etiologies, diagnostic means, emergency management, management result and delay of intervention. The data have processed on the Epi-Info version 3.5.1 2008. Results: Non traumatic urological emergencies have accounted for 6% of surgical emergencies and 92.7% of urological emergencies. The delay of consultation was average 3 years. The most common emergency was urine complete retention in 57.9% of cases and the main cause was benign prostatic hypertrophy (BPH) in 66% of cases. The average age was 61 years old (range: 15-86 years old). The sex ratio was 5.3. The urethral catheterization was practiced in 36 cases (47.6%). The main etiology of UCR was BPH in 29 cases (66%). Others etiologies as such as urethral stenosis, prostatic cancer and Bladder lithiasis followed in respectively 6 cases (13.6%), 5 cases (11.4%) and 4 cases (9%). The emergency has lifted in all cases. Conclusion: Management of non-traumatic urological emergencies has been quickly managed and if in doubt, exploratory surgery was needed
Keywords: Prevalence; Management; Non traumatic urological; Emergency